APPLYING THE RIGHT MEASURE: ARCHITECTURE AND PHILOLOGY IN BIBLICAL SCHOLARSHIP IN THE DUTCH EARLY ENLIGHTENMENT*. (29th October 2015) - Unknown
Abstract: The article reconstructs the seventeenth-century Dutch debate about the proper method to reconstruct the biblical temples of Jerusalem. It examines the involvement of Willem Goeree (1635–1711), an expert in architectural theory, in this debate which was dominated by philologically trained scholars. The article suggests that the clash between professional exegetes and a lay theologian like Goeree allows us to see hermeneutical debates of the early Enlightenment in a new light. While the skilled professional aspired to make arcane Temple scholarship accessible to a wider lay audience, theologians denied him the competence to do so, insisting on the primacy of sacred philology in interpreting the Bible. This case thus moves outside of the dogma vs reason dichotomy which dominates historiography concerning early modern biblical interpretation.